Circular Economy 4.0 Evaluation Model for Urban Road Infrastructure Projects, Ciroad - Derpich-Contreras, I; Venegas-Toledo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This paper provides a multicriteria evaluation model, based on the AHP methodology for the evaluation of the Circular Economy 4.0’s, which develops the metric called “Circularity indicator for urban road projects (CIROAD)”. The main contribution of this work is to provide a measurement scale specifically designed for urban road infrastructure projects. It is a useful tool to assess the degree of implementation of the principles of the Circular Economy (CE) and the Fourth Industrial Revolution (I4.0) in an integrated manner in these types of projects, generating valuable information for all stakeholders and contributing to the objective of accelerating the transition towards a Circular Economy 4.0 model in the construction industry. The model is defined with twenty-five sub-criteria and seven general criteria, which are: (1) Circular Materials; (2) Circular Design Approaches; (3) Circular Construction Approaches; (4) Circular Operation Approaches; (5) Approaches to Deconstruction and Resource Recovery; (6) Social Value Creation; and (7) Economic Performance. The developed CIROAD model was applied to three projects in the urban transport area of the Chilean Ministry of Housing and Urbanism (MINVU/SERVIU) in the Santiago Metropolitan Region (RM). In these three projects, low performance was observed in terms of CIROAD scores (between 21% and 28% of a maximum of 100%); that is, there is a significant opportunity for improvement by incorporating more circular practices in the development of projects by the studied organization. To accelerate the transition to a circular economy model in the development of its projects, it is proposed that the organization prioritize improving the following circular practices (in order of importance): (1) the design of pavements with environmental criteria; (2) preserving value; (3) conducting cost–benefit analysis (CBA) of waste management; (4) environmental declaration of materials (EPD); (5) the used of recycled materials; and (6) BIM-based design. Finally, the suggestion for the organization in charge of these projects is to use the developed CIROAD model as a tool to support decision making regarding the prioritization of its project portfolio. That is, the organization should use CIROAD to generate a ranking score for each project and allocate resources for investment in the initiatives that show the best circularity performances, as estimated by CIROAD. © 2023 by the authors.